Communication about early palliative care: A qualitative study of oncology providers’ perspectives of navigating the artful introduction to the palliative care team - Collins, Anna; Gurren, Lorna; McLachlan, Sue-Anne; Wawryk, Olivia; Philip, Jennifer (Frontiers in Oncology, 2022)
Background: Despite robust evidence for the integration of early palliative care for patients with advanced cancer, many patients still access this approach to care late. Communication about the introduction of Early Palliative Care is an important skill of healthcare providers working in this setting. In the context of limited community understanding about palliative care, patients and their families may express fear or negative reactions to its early introduction. Health professionals may lack the confidence or skill to describe the role and benefits of early palliative care. Aim: This study sought to explore clinicians’ perspectives on communication about referral to early palliative care, specifically identifying facilitators in undertaking this communication task. Methods: An exploratory qualitative study set within a tertiary oncology service in Victoria, Australia. Semi-structured interviews were conducted with purposively sampled oncology clinicians exploring their perspectives on communication about referral to early palliative care. A reflexive thematic analysis was undertaken by two researchers, including both latent and semantic coding relevant to the research question. Reporting of the research was guided by the Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist. Results: Twelve oncology clinicians (58% female, with 67% > 15 years clinical experience) from medical oncology, surgical oncology, and haematology participated. The artful navigation of communication about early palliative care was characterised by the need for a ‘spiel’ involving the adoption of a series of strategies or ‘tactics’ when introducing this service. These themes included: 1) Framing in terms of symptom control; 2) Framing as additive to patient care; 3) Selling the service benefits of early palliative care; 4) Framing acceptance of referral as an altruistic act; 5) Using carefully selected and rehearsed language; and 6) Adopting a phased approach to delivering information about palliative care. Implications: This study highlights the wide ranging and innovative communication strategies and skills required by health professionals to facilitate referral to early palliative care for cancer patients and their families. Future focus on upskilling clinicians around communication of this topic will be important to ensure successful implementation of models of early palliative care in routine cancer care.